2009
DOI: 10.1002/ejoc.200800882
|View full text |Cite
|
Sign up to set email alerts
|

Dizinc Phosphohydrolase Model Built on a m‐Terphenyl Scaffold and Its Use in Indicator Displacement Assays for Pyrophosphate Under Physiological Conditions

Abstract: A dinucleating ligand {1,3-bis[2-(di-2-picolylaminomethyl)-phenyl]benzene, L2} built on a m-terphenyl scaffold was prepared. The dissociation constants for the dizinc complex of L2 (Zn 2 L2) binding to phosphate, pyrophosphate and commercially available complexometric indicators were determined under physiological pH [10 mM N-(2-hydroxyethyl)piperazine-NЈ-2-ethanesulfonic acid (HEPES) buffer at pH 7.4]. Colorimetric and fluorescence-based indicator displacement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The same research group later reported receptor 50 based on a m-terphenyl scaffold for pyrophosphate-selective detection using IDAs. 69 The increase of the spacer distance between the two Zn(II)-DPA binding sites was expected to enhance selectivity for PPi over HPO 4 2À as compared to receptor 47. Both colorimetric indicators (MX, PAR, PV and ZC) and a fluorescent indicator (ESC) were employed in IDAs to study the binding affinity of 50 for PPi.…”
Section: àmentioning
confidence: 99%
“…The same research group later reported receptor 50 based on a m-terphenyl scaffold for pyrophosphate-selective detection using IDAs. 69 The increase of the spacer distance between the two Zn(II)-DPA binding sites was expected to enhance selectivity for PPi over HPO 4 2À as compared to receptor 47. Both colorimetric indicators (MX, PAR, PV and ZC) and a fluorescent indicator (ESC) were employed in IDAs to study the binding affinity of 50 for PPi.…”
Section: àmentioning
confidence: 99%
“…Although recent advances in receptor development have identied several sensors capable of selectively recognizing PPi in water, selectivity for the binding of PPi over other polyphosphate oxoanions such as ATP and ADP remains modest and in general is unsuitable for practical use. [9][10][11][12][13][14][15][16][17][18][19][20][21] Furthermore, very few PPi sensors have been shown to operate in biologically relevant media, where high salt concentrations and the presence of a range of competing anions and cations are expected to affect both the binding affinity and selectivity. 22 Indicator displacement assays (IDAs) have been widely used for the sensing of anionic species.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Chemosensors based on the complex have been developed by utilizinga nion exchange at the vacants ite of the zinc ions, and appliedf or the detection of phosphate derivatives. [28][29][30][31][32][33][34] Several attempts have been made to introduce functional groupss uch as chromophores, fluorophores, and redox-active complexes on the phenol moiety in the bpmp complex, and some of them were applied to chemosensors that show enhanced signalv isibility. [35][36][37][38][39][40][41][42][43] Recently, we reported ad ye-conjugatedc omplex, composed of at riarylmethane( TAM) dye moiety and aZ nbpmpc omplex moiety.…”
Section: Introductionmentioning
confidence: 99%
“…As a ligand, bpmp forms a μ‐phenoxo‐bridged dinuclear zinc complex with some extra anions . Chemosensors based on the complex have been developed by utilizing anion exchange at the vacant site of the zinc ions, and applied for the detection of phosphate derivatives . Several attempts have been made to introduce functional groups such as chromophores, fluorophores, and redox‐active complexes on the phenol moiety in the bpmp complex, and some of them were applied to chemosensors that show enhanced signal visibility .…”
Section: Introductionmentioning
confidence: 99%